Psychological Immunity and its Relationship to Some Variables in a Sample of Sudanese during the 2023 War - Babiker, Mona Hassan (Dirasat: Educational Sciences, 2025)
Objectives: The study aimed to examine the level of psychological immunity among a sample of Sudanese individuals during the Sudan War of 2023 and to identify differences in psychological immunity levels based on demographic variables (gender, age, and educational level). Methods: To achieve the study’s objectives, a descriptive approach was adopted, and a scale was developed to assess psychological immunity levels. The scale consisted of 97 items distributed across ten dimensions. The study sample included 832 displaced persons and refugees from Khartoum State. Results: The findings indicated that the level of psychological immunity among the Sudanese sample during the 2023 war was moderate. Additionally, the study revealed no significant differences in psychological immunity levels based on gender and educational level. However, there were significant differences based on age, particularly between the age groups of 36-45 years and those under 25 years, in favor of the 46-55 age group. Conclusions: The study recommends implementing counseling and therapeutic programs for displaced persons and refugees to enhance their psychological immunity and reduce psychological stressors that may negatively impact their mental health.